2021
DOI: 10.1038/s41531-021-00216-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic biomarkers of Parkinson’s disease in the Spanish EPIC cohort: a multiplatform metabolomics approach

Abstract: The lack of knowledge about the onset and progression of Parkinson’s disease (PD) hampers its early diagnosis and treatment. Metabolomics might shed light on the PD imprint seeking a broader view of the biochemical remodeling induced by this disease in an early and pre-symptomatic stage and unveiling potential biomarkers. To achieve this goal, we took advantage of the great potential of the European Prospective Study on Nutrition and Cancer (EPIC) cohort to apply metabolomics searching for early diagnostic PD … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 62 publications
5
70
1
Order By: Relevance
“…Levels of other proteinogenic amino acids are also reduced in DJ-1β mutant flies. For example, they present decreased tryptophan levels, whose metabolism is related to neurodegeneration in PD patients at early stages [46,65,68]. Another proteinogenic amino acid affected in DJ-1β mutants is glycine, a small amino acid with neuroprotective effects in neuroinflammation, ROS-related damage, and synaptic dysfunction through JNK signaling inactivation [69].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of other proteinogenic amino acids are also reduced in DJ-1β mutant flies. For example, they present decreased tryptophan levels, whose metabolism is related to neurodegeneration in PD patients at early stages [46,65,68]. Another proteinogenic amino acid affected in DJ-1β mutants is glycine, a small amino acid with neuroprotective effects in neuroinflammation, ROS-related damage, and synaptic dysfunction through JNK signaling inactivation [69].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of other proteinogenic amino acids are also reduced in DJ-1β mutant flies. For example, they present decreased tryptophan levels whose metabolism has been related to neurodegeneration in PD patients at early stages [42,61,64]. Another proteinogenic amino acid affected in DJ-1β mutants is glycine, a small amino acid with neuroprotective effects in neuroinflammation, ROS-related damage, and synaptic dysfunction through JNK signalling inactivation [65].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have approached the relationship between PA and PD [ 24 , 25 , 114 , 180 , 202 ]. In that sense, Shah et al, (2019) injected Sprague-Dawley rats unilaterally with 6-hydroxydopamine into the medial forebrain bundle to induce a loss of dopaminergic neurons in the substantia nigra, as a PD model.…”
Section: Palmitic Acid and Neurogenerative Diseasesmentioning
confidence: 99%
“…On the other side, recent evidence from Gonzalez-Riano et al, (2021), using a metabolomics approach to find PD biomarkers in the Spanish population, found a significant reduction of plasma PA in pre-PD subjects and they hypothesized that it was due to an early and progressive migration of PA from the plasma to the brain because ASN promoted the uptake of PA into the brain [ 202 ]. Besides, a reduced expression of peroxisome proliferator-activated receptor-gamma coactivator−1 α (PGC−1α) was found in affected brain tissue from PD patients, and it was found that PA stimulates PGC−1α promoter methylation in mouse primary cortical neurons, microglia, and astrocytes.…”
Section: Palmitic Acid and Neurogenerative Diseasesmentioning
confidence: 99%